The Effectiveness of Development of Brain-Based Arabic Learning Media with a Neuroscience Approach to Muhammadiyah Vocational High School Students in the COVID-19 Period - Jailani, Mohammad (Andragogi: Jurnal Diklat Teknis Pendidikan dan Keagamaan, 2024)
The problem in SMK Muhammadiyah 3 Yogyakarta is that students cannot understand Arabic well due to conventional techniques and textbook-based learning. This study aimed to develop Arabic learning media based on neuroscience in SMK Muhammadiyah 3 Yogyakarta. Neuroscience, as the learning media, has the goal of improving students' learning outcomes. The data were obtained from documents, namely the classification of reputable National and International journals, along with interviews with 20 students and 2 teachers. The study's results prove that Arabic learning media based on neuroscience could improve students' learning outcomes in the Arabic language with an average score of 77.58/B+. The combination of attractive learning media and neuroscience theory is proven to be an effective approach that could stimulate students. The analysis of learning media based on neuroscience, from the stages of product design, development, and evaluation to revision, results in data that shows that student learning outcomes were well arranged. The weakness of neuroscience as the Arabic learning media was in the results of students' population data, in which only a few students did not show improvement in learning Arabic. However, at general, implications of developing Arabic learning media based on neuroscience could provide creativity to teachers and help the students in learning Arabic, especially in SMK Muhammadiyah 3 Yogyakarta. Therefore, the development of neuroscience as an Arabic learning media requires further research. (Pokok masalah di SMK Muhammadiyah 3 Yogyakarta adalah Bahasa Arab yang tidak dapat dipahami siswa karena pembelajaran masih bersifat konvensional dan tingginya ketergantungan terhadap bahan buku ajar. Penelitian ini bertujuan mengembangkan media pembelajaran Bahasa Arab berbasis neuroscience di SMK Muhammadiyah 3 Yogyakarta. Neuroscience sebagai media pembelajaran memiliki tujuan untuk meningkatkan hasil belajar siswa. Data diperoleh dari dokumen, yakni klasifikasi jurnal Nasional dan Internasional bereputasi serta wawancara kepada 20 siswa dan 2 guru. Hasil penelitian membuktikan bahwa media pembelajaran bahasa Arab berbasis neuroscience dapat meningkatkan hasil belajar siswa dalam pembelajaran Bahasa Arab dengan nilai rata-rata 77,58/B+. Kombinasi media pembelajaran yang menarik dan teori neuroscience terbukti merupakan pendekatan yang dapat merangsang siswa. Analisis media pembelajaran berdasarkan neuroscience hingga tahapan desain produk, pengembangan, evaluasi dan revisi menghasilkan data bahwa hasil belajar siswa tersusun dengan baik. Kelemahan neuroscience sebagai media pembelajaran Bahasa Arab terdapat pada hasil data populasi di mana segelintir siswa tetap tidak menunjukkan kemajuan dalam memahami Bahasa Arab. Meski demikian, secara umum, penerapan pengembangan media pembelajaran Bahasa Arab berbasis neuroscience dapat memberikan kreativitas kepada guru dan membantu siswa dalam pembelajaran Bahasa Arab khususnya di SMK Muhammadiyah 3 Yogyakarta. Oleh karena itu, pengembangan neuroscience sebagai media pembelajaran bahasa Arab memerlakukan penelitian lebih lanjut.)